Chemically transformed monolayers on acene thin films for improved metal/organic interfaces. Issue 93 (5th November 2019) - Li, Feifei; Hopwood, Jonathan P.; Galey, Melissa M.; Sanchez, Laura M.; Ciszek, Jacob W.
Abstract : Chemically installed functional groups on top of organic semiconductors allow for improved adhesion with metal top contacts. Abstract : Anhydride terminated acene thin films were chemically transformed to thiol or carboxylic acid functionalities, groups heretofore incompatible with monolayer reactions. The molecular surface imparts large rate acceleration when imides are formed, while disfavored disulfides can be formed from the thiols. The modified surface imparts improved adhesion to top metal contacts in flexible/bendable applications.